PENERAPAN DISCOVERY LEARNING BERBANTUAN MEDIA TIGA DIMENSI UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA MATERI BANGUN RUANG DI SDK ANUGERAH HAUKOTO - Benu, Adam Bol Nifu; Sortuy, Pamela N.; Dominikus, Wara Sabon (Universitas Nusa Cendana, 2024)
Abstract: The aim of this research is to describe the application of the Discovery Learning model assisted by three-dimensional media in mathematics learning about spatial material, determine the increase in student activity after implementing the Discovery Learning model assisted by three-dimensional media, and determine the increase in student learning outcomes. Data collection techniques are observation, testing and documentation techniques, with research subjects as many as 8 students. Data analysis techniques are descriptive qualitative and quantitative. This research was carried out at SDK Anugerah Haukoto with the results showing that the first cycle of the number of students was 8 people, 5 people (62.5%) completed it. In cycle II the number of students who completed was 8 people with a percentage of 100%. Based on the results of the research, it can be concluded that the application of the Discovery Learning model assisted by three-dimensional media can improve student learning outcomes, especially in learning mathematics regarding geometric material.